An exact algorithm for the reliability redundancy allocation problem - Caserta, Marco; Voß, Stefan (European journal of operational research, 2015)
•New exact algorithm for the redundancy allocation problem.•Applying a two-step problem transformation to the multiple choice knapsack problem.•Considerable improvements in running time and solution quality over earlier methods. The redundancy allocation problem is the problem of finding an optimal allocation of redundant components subject to a set of resource constraints. The problem studied in this paper refers to a series-parallel system configuration and allows for component mixing. We propose a new modeling/solution approach, in which the problem is transformed into a multiple choice knapsack problem and solved to optimality via a branch and cut algorithm. The algorithm is tested on well-known sets of benchmark instances. All instances have been solved to optimality in milliseconds or very few seconds on a normal workstation.